2012
DOI: 10.1002/jso.23033
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative change in peripheral blood monocyte count may predict prognosis in patients with colorectal liver metastasis after hepatic resection

Abstract: Perioperative change in peripheral blood monocyte count is an independent risk factor for overall survival after hepatic resection for CRLM, and may reflect immunosuppressive state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…A correlation between monocytosis and poor prognosis in different types of cancer has previously been observed (16,(25)(26)(27). Monocytes represent a source of chemokines and cytokines that contribute to inflammation (28).…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 89%
“…A correlation between monocytosis and poor prognosis in different types of cancer has previously been observed (16,(25)(26)(27). Monocytes represent a source of chemokines and cytokines that contribute to inflammation (28).…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 89%
“…The Glasgow prognostic score (GPS), which is calculated by the combination of serum C-reactive protein (CRP) and albumin concentrations, and the elevated preoperative neutrophil-to-lymphocyte ratio (NLR), have been revealed to predict cancer-specific survival (7)(8)(9)(10)(11)(12). The previous study reported negative impact of GPS on post-operative complications following hepatic resection (13,14), and the association between perioperative immunological response and prognosis subsequent to hepatic resection for HCC (15,16) and CRLM (17). In the present study, the association between preoperative peripheral blood neutrophil count and disease-free, as well as overall survival, following elective hepatic resection for patients with CRLM was retrospectively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Reportedly, preoperative variables, including decreased lymphocyte count, increased monocyte count, and elevated neutrophil‐to‐lymphocyte ratio, are associated with poor prognosis in cancer patients 32, 33. In addition, perioperative changes in peripheral blood monocyte counts are independent risk factors for OS after hepatectomy and may reflect an immunosuppressive state 34. In this study, PBMC and LMNC counts, including those of lymphocytes and monocytes, of the group receiving neoadjuvant chemotherapy were not less than those of the group primarily receiving hepatectomy.…”
Section: Discussionmentioning
confidence: 99%